Decreased phrenic nerve compound muscle action potential, inspiratory muscle strength, and exercise capacity after COVID-19 - Vonbank, Karin; Nics, Helena; Zwick, Ralf Harun; Maasz, Julia; Sabic, Benjamin; Potzmann, Marijan; Brandhofer, Georg; Fuchs, Julia; Yeghiazaryan, Lusine; Burtscher, Martin; Paternostro-Sluga, Tatjana (Frontiers in Neurology, 2024)
Objectives Respiratory muscle weakness with higher ventilatory demands were reported even in patients recovering from only mild COVID-19 symptoms. Aim of this study was to assess the function of phrenic nerve and inspiratory respiratory muscle as well as cardiopulmonary exercise capacity in patients with prolonged exertional dyspnea after COVID-19 infection. Methods In this observational exploratory study, electrophysiological examination of the phrenic nerve, inspiratory muscle capacity as well as lung function test, 6-min walk distance (6MWD) and cardiopulmonary exercise test, have been performed in 22 patients post COVID-19 diagnosis (post-CoV). Results Exercise capacity (peak workload, Wpeak % predicted and peak oxygen uptake, VO2peak % predicted) were significantly affected in the post-CoV patients (61.8 ± 23.3 Wpeak % and 70.9 ± 22.3 VO2peak %). Maximum inspiratory pressure (MIP) was reduced (60.1 ± 25.5 mbar). In 6 of the 22 patients the electrophysiological response of the phrenic nerve was pathologically decreased (reduced compound muscle action potential, CMAP), while nerve conduction velocity (NCV) was normal, which corresponds to reduced muscle fiber contraction capacity. Positive relationships were demonstrated between 6MWD and MIP (rs = 0.88) as well as quality of life questionnaire (CRQ) and MIP (rs = 0.71) only in patients with reduced CMAP. Discussion Respiratory muscle weakness and exercise capacity is associated with reduced phrenic nerve CMAP without signs of neuropathy. This indicates that muscle fiber pathology of the diaphragm may be one pathophysiological factor for the prolonged respiratory symptoms after COVID-19 infections.